1000FARMS Annual Meeting Report 2025 - 1000FARMS Platform (Bioversity International and International Center for Tropical Agriculture, 2025)
The 1000FARMS project aims to establish an Africa-wide network for on-farm testing. The project started in late 2021 and is funded by the Gates Foundation (GF) and implementation is done in partnership between the Alliance of Bioversity International and CIAT (project lead), IITA, CIMMYT, INN University (until 2023), and Wageningen University. The project works intensively with CGIAR-NARES breeding networks through other CGIAR-led projects. The 1000FARMS team held the final annual stakeholders meeting for the project in Harare, Zimbabwe from 1 to 3 October 2025. This convening brought together the project team, partners, and funders to discuss project progress to date, lessons learned and to plan future work, with a focus on addressing key gaps and harnessing emerging opportunities. This report shares the main insights from the meeting.